The relationship between individual factors and career adaptability among fresh graduates: results from a pilot test - Anas, Ilyana; Hamzah, Siti Raba'ah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Declining global growth has slowed human resource development such as job skill mismatches is part of the present challenges in Malaysia. Due to this challenge, continuous career adaptation to the world of work is crucial in order to make changes in self for satisfaction and to be successful in life. This study is sought to investigate and conduct preliminary investigation of the individual factors that contribute towards career adaptability. We focus on the career adaptability which are related to self-esteem, conscientiousness, spiritual intelligence, and social support. A quantitative and cross-sectional survey has been chosen as the research design for this study. We proposed that all dimensions have positive relationship and contribute significantly towards career adaptability. Fresh graduate employees (n=30) from different public universities has been selected to participate in pilot test to determine the reliability of the instrument. The Cronbach’s Alpha (α) result was showed for all dimensions. The implication of this study is hope to improve the method for future researchers and to give awareness to fresh graduates or to whom it may concern on the importance of career adaptability.